2016
DOI: 10.1155/2016/6918327
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Continuous S(+)-Ketamine Infusion for Postoperative Pain Control: A Randomized Placebo-Controlled Trial

Abstract: Aim. A double-blind, randomized, placebo-controlled trial was designed to evaluate the efficacy of continuous intraoperative infusion of S(+)-ketamine under intravenous anesthesia with target-controlled infusion of remifentanil and propofol for postoperative pain control. Methods. Forty-eight patients undergoing laparoscopic cholecystectomy were assigned to receive continuous S(+)-ketamine infusion at a rate of 0.3 mg·kg−1·h−1 (n = 24, intervention group) or an equivalent volume of saline at the same rate (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 27 publications
0
21
0
3
Order By: Relevance
“… 65 Continuous S(+)-ketamine infusion during laparoscopic cholecystectomy provided better postoperative pain control in the PACU than placebo. 66 Racemic mixtures of ketamine are neurotoxic, the neuraxial use of which is strongly discouraged. In fact, a recent study revealed that the addition of ketamine (1 mg/kg) to 0.1% ropivacaine via continuous femoral block with pump infusion after repairing anterior cruciate ligament could not improve postoperative pain control.…”
Section: Pharmacological Managementmentioning
confidence: 99%
“… 65 Continuous S(+)-ketamine infusion during laparoscopic cholecystectomy provided better postoperative pain control in the PACU than placebo. 66 Racemic mixtures of ketamine are neurotoxic, the neuraxial use of which is strongly discouraged. In fact, a recent study revealed that the addition of ketamine (1 mg/kg) to 0.1% ropivacaine via continuous femoral block with pump infusion after repairing anterior cruciate ligament could not improve postoperative pain control.…”
Section: Pharmacological Managementmentioning
confidence: 99%
“…A observação da FC nos cães GA mostra elevação do parâmetro, confirmando a ação simpatomimética da cetamina (MIZIARA et al, 2016). Esse fenômeno simpatomimético pode ser explicado pela interferência do fármaco na receptação de noradrenalina e catecolaminas (SELMI et al 2005).…”
Section: Resultsunclassified
“…A administração de midazolan concomitante à cetamina minimiza o efeito estimulante cardiovascular (CANFRAN, et al,2016), e os fenotiazínicos e opióides promovem bradicardia atenuando a ação do anestésico dissociativo (MIZIARA et al, 2016). Neste estudo, com intenção de minimizar os efeitos da cetamina, no GA (P1) foram administrados na MPA acepromazina e fentanil, porém, ainda percebeu-se presença de elevação no ritmo e frequência cardíaca constante, mas, sem significância durante todos os tempos analisados de transoperatório com o efeito de manipulação abdominal.…”
Section: Resultsunclassified
“…Study by Miziara et al showed that S(+)-ketamine infusion in laparoscopic cholecystectomy resulted in better postoperative pain control than the placebo group. 17 Therefore, injection of a single dose of ketamine, which acts short-acting both before and after the incision, will not produce analgesia that lasts long into the postoperative period. Besides, setting a constant serum concentration is also needed to achieve the required analgesia effect.…”
Section: Discussionmentioning
confidence: 99%